2023
DOI: 10.21203/rs.3.rs-3410701/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IRF4 affects the protective effect of regulatory T cells on the pulmonary vasculature of a bronchopulmonary dysplasia mouse model by regulating FOXP3

Ying Zhu,
Langyue He,
Yue Zhu
et al.

Abstract: Background Bronchopulmonary dysplasia (BPD) is a common chronic lung disease in preterm infants, characterised by compromised alveolar development and pulmonary vascular abnormalities. Emerging evidence suggests that regulatory T cells (Tregs) may confer protective effects on the vasculature. Knockdown of their transcription factor, interferon regulatory factor 4 (IRF4), has been shown to promote vascular endothelial hyperplasia. However, the involvement of Tregs and IRF4 in the BPD pathogenesis remains uncle… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Miroslaw et al [41] determined that hyperoxia exposure can result in altered genomic activity and elevated levels of oxidative stress in lung cells. Our previous studies found that long-term hyperoxia exposure also contributes to vascular endothelial growth factor and angiopoietin-1, resulting in impaired lung development [42]. Currently, neonatal mice exposed to high oxygen levels are a relatively mature animal model for BPD [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Miroslaw et al [41] determined that hyperoxia exposure can result in altered genomic activity and elevated levels of oxidative stress in lung cells. Our previous studies found that long-term hyperoxia exposure also contributes to vascular endothelial growth factor and angiopoietin-1, resulting in impaired lung development [42]. Currently, neonatal mice exposed to high oxygen levels are a relatively mature animal model for BPD [29,30].…”
Section: Discussionmentioning
confidence: 99%